2021
DOI: 10.1002/rmv.2268
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming and immune regulation in viral diseases

Abstract: The recent outbreak and transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) worldwide and the ensuing coronavirus disease 2019 (COVID-19) pandemic has left us scrambling for ways to contain the disease and develop vaccines that are safe and effective. Equally important, understanding the impact of the virus on the host system in convalescent patients, healthy otherwise or with co-morbidities, is expected to aid in developing effective strategies in the management of patients afflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 163 publications
0
19
0
Order By: Relevance
“…The molecular basis of COVID-19’s dysregulated glucose metabolism is poorly understood. The discovery of the molecular processes used by viruses and cancers in their host metabolism expands the therapeutic toolbox available to fight viral disease [ 38 , 39 ]. Although viral infection is known to alter host cell metabolism for more than half a century, the processes and effects of virus-induced metabolic reprogramming have been examined in depth only recently.…”
Section: Inflammation and Associated Diseasesmentioning
confidence: 99%
“…The molecular basis of COVID-19’s dysregulated glucose metabolism is poorly understood. The discovery of the molecular processes used by viruses and cancers in their host metabolism expands the therapeutic toolbox available to fight viral disease [ 38 , 39 ]. Although viral infection is known to alter host cell metabolism for more than half a century, the processes and effects of virus-induced metabolic reprogramming have been examined in depth only recently.…”
Section: Inflammation and Associated Diseasesmentioning
confidence: 99%
“…46 Some viral proteins employ host metabolic activities to induce dysregulation in various cellular pathways, increasing cancer risk. 43 For example, the human papillomavirus 16 E6 protein inhibited hypoxia-inducing factor-alpha (HIF-α) degradation and thereby enhanced glycolysis in cells infected with this virus. 47 In Vero cells, it has been found that Enterovirus EV71 can increase glutamine metabolism, whereas pharmaceutical suppression of pyrimidine metabolism enzymes reduced viral proliferation.…”
Section: Overview Of Host Metabolic Reprogramming During Viral Infect...mentioning
confidence: 99%
“…61,67 Iron is thought to be involved in the cellular metabolism of all living organisms, such as viruses and their mammalian hosts. 43 A differing class of mediators tightly regulates the host's concentration of iron is circulating, including both unbound and heme-bound forms, in a way that mitigates oxidative injury (iron-mediated) and postpones the migration and development of pathogenic organisms both extracellularly (as in blood that harbor's specific parasites and bacteria) and inside cells (as fundamentally observed with viruses). 43 Although most intrinsic iron is recycled through the formation and destruction of erythrocytes, cells also have complicated systems for iron storage.…”
Section: Overview Of Host Metabolic Reprogramming During Viral Infect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic Reprogramming is a phenomenon observed in cancer, viral infection, and neurodegenerative diseases [ 5 , 6 , 7 , 8 , 9 ], which results in the rewiring of the cellular metabolism to support the increasing energy demand. Cancer cells and viruses use this mechanism to synthesize free nucleotides and amino acids necessary for their assembly and replication [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%